KURSUS SINGKAT DAN PELATIHAN PENGOLAHAN SALAK MENJADI DODOL SALAK DI DESA SIBETAN KECAMATAN BEBANDEM KABUPATEN KARANGASEM - SUARYA, PUTU; SUDIARTA, I WAYAN; ANGGRENI, ANAK AGUNG MADE DEWI; PUSPAWATI, NI NYOMAN; TRIANI, I G A LANI (Buletin Udayana Mengabdi, 2012)
ABSTRACT The farmers of salaks, the snake fruits of Sibetan Village have encountered the price tumble during the harvest time. The bumper crops during the harvest while at the same time there is a steady demand on it, as well as that there has not been an effort to process the abundant crops into a preserved foods are considered to be the main factors that cause its price drop.Training and short course have been conducted to introduce the way how to process the fruits into dodol salak, a sticky cake made of the salak fruit as the main material, by conducting the lecturing and practicing method. The participants were members of family welfare organization (PKK) and the local housewives from Telutug of Sibetan village with the total number of 32 participants, and most of them are the farmers of salaks. The process of making the dodol salak comprises the following steps : the collection and selection of the fruits, peeling and coring the fruit, steaming, mashing the fruits into a pulp, the mixing with coconut milk, palm sugar and sticky rice floor in the bowl, mixing and boiling the mixture within 120 minutes, cooling down and then it is molded and wrapped.The result of the training shows that the participants were really enthusiastic, it could be seen by the abundant of questions raised either during the lecture, discussion as well as during the practice of making the dodol salak itself. It is expected that by introducing the way how to process the fruits into dodol will improve the skill and knowledge of the local people in general and especially for those of PKK members and the housewives. The food processing into dodol salak may bring about many advantages such as the diversification of the fruit processed-product, giving the added value to the fruit, to lengthen the storage time and to improve the appearance and quality of the product.